The role of costs’ knowledge in the contemporary enterprises - Łazarczyk, Damian (Ekonomia i Prawo. Economics and Law, 2020)
Motivation: Contemporary enterprises need useful information to reach success in times of globalization of market economy. Costs are an indispensable economic category, especially in decision process. Costs constitute the wear and tear expressed in the financial measure. Generating costs is reflecting the manner of the conducting business activities. Costs are incurred to reach the income. Cost is inevitable, whereas income is probable. Therefore, cost control and cost management matter. The information about cost is primarily used for: regulating the prices, closing the decisional cost and result accounts, providing ‘activity based costing’ analyses (including contemporary ‘time-driven activity based costing’), as well as budgeting the operational and control costs. The development of cost accounting systems results from globalization and growth in importance of the knowledge in managing contemporary enterprises. Essential premises of the development include: loss of timelines of the reporting cost accounting, rise in the automation and technology in the production, rise in the share of indirect costs in all-in costs and increase in the usefulness of the knowledge for the costs indirect, dynamic growth of the role of information in the business administration, increase in the costing awareness of managers. Aim: This article’s research aim is to explain the influence of cost accounting instrumentation on managing contemporary enterprises, including the decision-making process. Results: Knowledge about costs getting from cost accounting, have a significant impact on a contemporary enterprise management.